The Impact of Arab Nationali sm upon Arab Solidarity in the New Millennium: Reality and Dimension. - Kashiem, Dr.Mustafa (Dirasat in Economics and Business, 2009)
Although the famous Amer- ican political scientist Francis Fukuyrama, concluded in his outstanding book entitled the End of History that r.he age of ideology is gone forever when ex sovier bloc collapsed in the late 1980s and early 1990s, but the evidenecs demonstrate that ideologies do exist as far as civi lizations and peoples are alive. Arab nationalism, as an Ideo- logy, is a prominent political !actor that affected inter Arab relations since the era of anti -colonialism. This study assumes that Arab nationalism as an Ideo logy is expected to influence the level of cohesion towards matters of common interests. Methodologically speaking, this study dealt with Arab nation alism as an independent variab- le, and Arab solidarity as a dep- endent variable. Thus, Arab na -tionalism resulted, as an ideo logical factor in a cohesive Arab position vis-a-vis its ene. mies during the era of colonj. alism and post independence periods. Furthermore, Arab na -tionalism is a crucial factor that distinguish Arabism in the age of globalization, where sovere ignty and political border are deemphasized noticeably.